Assessing the impacts of normative and efficacy‐based messaging on the social diffusion of conservation science. Issue 4 (24th February 2022) - Berl, Richard E. W.; Sekar, Samantha; Markevich, Anyll; Camara, Cassiopeia; Niemiec, Rebecca M.
Abstract: Encouraging people to share science‐based information on environmental issues with others is critical for enhancing the speed and scale of conservation action. However, little experimental research exists that examines how message framing can facilitate the social diffusion of scientific information. We report the results of a series of studies conducted to test the effects of normative and efficacy‐based messaging on Colorado residents' willingness to share scientific information about the state's wolf reintroduction initiative. We distributed messaging using mailings to the general public, surveys of online participant panels, and personal messages from undergraduate students to their own contacts. We then measured participants' individual engagement with the scientific information we provided and their engagement in social behaviors that would encourage further social diffusion of the information. While we find some evidence of increased engagement by people contacted through social diffusion, we do not find any evidence that normative and efficacy‐based messaging encourages people to engage in social diffusion, nor do we find that such messaging enhances individual engagement with the scientific information. We identify several barriers to the sharing of scientific information, which could inform the development of future interventions to scale up biodiversity conservation efforts beyond individual engagement through widespread social diffusion.